Comparative efficacy and safety of the duodenal-jejunal bypass liner in obese patients with type 2 diabetes mellitus – a case control study - Katharina Laubner and Nina Riedel and Katharina Fink and Reinhard W. Holl and Reinhard Welp and Hans-Peter Kempe and Anne Lautenbach and Matthias Schlensak and Rainer Stengel and Thomas Eberl and Frank Dederichs and Henning Schwacha and Jochen Seufer and Jens Aberle (Diabetes, obesity and metabolism, 2018)
Abstract